Umbilical artery thrombosis diagnosed at different gestational ages and fetal outcomes: a case series - Jing Wei; Qiaoyun Li; Hongbo Zhai (BMC, 2021)
Abstract Background Umbilical artery thrombosis is a rare complication of pregnancy strongly associated with poor fetal and perinatal outcomes, such as intrauterine asphyxia, fetal growth restriction, and stillbirth. Its pathogenesis remains unclear, and there is the added challenge of selecting an appropriate delivery time to achieve excellent neonatal outcomes. Methods Our Hospital is a critical maternal rescue center with approximately 7000 births annually. We present a series of 8 cases of umbilical artery thrombosis diagnosed at the hospital between Apr 1, 2018, and Jan 31, 2020. We identified the cases through a keyword search of the maternity and pathology information management systems. Results Three patients were diagnosed with a transabdominal ultrasound scan and hypoxia on fetal heart monitoring. All three patients had emergency cesarean section delivery. Four patients were observed closely for 5 to 13 weeks from initial detection by an ultrasound scan to delivery. Only one patient was diagnosed after vaginal delivery by Hematoxylin-eosin staining of umbilical cord sections. Seven patients had deliveries by cesarean section, and one patient had a vaginal delivery. All infants were born alive. Conclusions Umbilical artery thrombosis is a challenging and rare condition that can occur at different gestational ages, especially when diagnosed in the third trimester and accompanied by fetal growth restriction. Consequently, these patients require close monitoring of umbilical blood flow and fetal growth and intervention at the appropriate time to achieve an optimal outcome.